The Use of Therapeutic Outcome Measures by Australian Psychotherapists and Counsellors - Alexandra Bloch-Atefi; Elizabeth Day (Psychotherapy and Counselling Journal of Australia)
# Background Outcome measures are increasingly emphasised as effective tools in Australian mental health policy. However, limited understanding exists about usage patterns and barriers among counsellors and psychotherapists practising in Australia. This study addresses this gap by examining the prevalence, usage, and perceptions of outcome measures within the Australian counselling and psychotherapy workforce. # Objectives This study explored whether and why members of the Psychotherapy and Counselling Federation of Australia (PACFA) use outcome measures and identified what factors influence their choices. # Method A mixed-methods design was used, combining quantitative and qualitative data from an online survey distributed to PACFA members. A total of 1,177 respondents participated, representing 34% of PACFA’s registered clinicians. Quantitative data were analysed using descriptive statistics via the Statistical Package for the Social Sciences, and qualitative responses were analysed thematically. # Results The majority of respondents (76.6%) used outcome measures regularly, primarily because of institutional requirements and their utility in tracking client progress. Barriers included time constraints, complexity of use and evaluation of the measures, and perceived misalignment with client-centred approaches. Non-users cited concerns about the incompatibility of standardised tools with therapeutic models focused on relational dynamics. # Conclusions/Implications The study finds a need for outcome measures that align with diverse therapeutic approaches and for training practitioners to use them effectively. These findings are timely as the Australian government moves towards establishing national standards for the sector and have implications for policy, practice, and professional development. Future research should focus on developing flexible, user-friendly tools and addressing barriers to their adoption in both public and private practice settings.